A Rapid and Highly Efficient Method for Transient Gene Expression in Rice Plants - Burman, Naini; Chandran, Divya; Khurana, Jitendra P. (Frontiers in Plant Science, 2020)
Rice is the model plant system for monocots and the sequencing of its genome has led to the identification of a vast array of genes for characterisation. The tedious and time-consuming effort of raising rice transgenics has significantly delayed the pace of rice research. The lack of highly efficient transient assay protocol for rice has only added to the woes which could have otherwise helped in rapid deciphering of the functions of genes. Here, we describe a technique for efficient transient gene expression in rice seedlings. It makes use of co-cultivation of 6-day-old rice seedlings with Agrobacterium in the presence of a medium containing Silwet® L-77, acetosyringone and glucose. Seedlings can be visualised 9 days after co-cultivation for transient expression. The use of young seedlings helps in significantly reducing the duration of the experiment and facilitates the visualisation of rice cells under the microscope as young leaves are thinner than mature rice leaves. Further, growth of seedlings at low temperature, and the use of surfactant along with wounding and vacuum infiltration steps significantly increases the efficiency of this protocol and helps in bypassing the natural barriers in rice leaves, which hinders Agrobacterium-based transformation in this plant. This technique, therefore, provides a shorter, efficient and cost-effective way to study transient gene function in intact rice seedling without the need for a specialised device like particle gun.